1992
DOI: 10.1002/ijc.2910520117
|View full text |Cite
|
Sign up to set email alerts
|

Single‐step transformation of human breast epithelial cells by SV40 large T oncogene

Abstract: Normal human mammary epithelial cell (HMEC) cultures originating from 2 mammoplasty reduction surgical samples were transfected with replication-defective SV 40 DNA. Two independent cell lines designated as S2T2 and S1T3, selected for their increased proliferation potential and lifespan, were propagated for greater than 22 months in culture. They maintained a near-diploid karyotype with few chromosomal markers such as trisomy 1q (S1T3) and trisomy 8q (S2T2), which are most common in breast cancer in vivo. Immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Our results appear to confirm that the expression of the SV40 T Ag gene in breast epithelial cells may directly cause Cytok-ai manuny cds trumssormed by Ad5/SV40 viru F Basolo et ai 1361 the appearance of a malignant phenotype (Berthon et al, 1992). The phenotypic differences between non-tumorigenic Ml and tumorigenic M2 cells are, however, unclear and not due to detectable p53 mutations.…”
Section: Analysis Of P53 Mutationssupporting
confidence: 67%
See 1 more Smart Citation
“…Our results appear to confirm that the expression of the SV40 T Ag gene in breast epithelial cells may directly cause Cytok-ai manuny cds trumssormed by Ad5/SV40 viru F Basolo et ai 1361 the appearance of a malignant phenotype (Berthon et al, 1992). The phenotypic differences between non-tumorigenic Ml and tumorigenic M2 cells are, however, unclear and not due to detectable p53 mutations.…”
Section: Analysis Of P53 Mutationssupporting
confidence: 67%
“…Several human breast cancer cell lines have already been obtained in different laboratories (O'Hire, 1991), but only a few human MEC lines have been derived from normal breast tissue (Soule et al, 1990;Paine et al, 1992). Owing to the extremely low frequency of spontaneous immortalisation, MEC lines have been established either by chemical treatment, by transfection with different oncogenes or by infection with oncogenic viruses (Calaf and Russo, 1993;Ciardiello et al, 1993;Ochieng et al, 1991;Berthon et al, 1992). We used a replication-defective recombinant adeno-5/SV40 virus (Ad5/SV40) that carries the adenovirus type 5 capsid, the early genomic adenovirus region lacking the origin of replication, and the SV40 large T antigen (SV40 T Ag; Van Doren and Gluzman, 1984).…”
mentioning
confidence: 99%
“…Three cell lines reflecting three distinct molecular states with respect to PTHrP mRNA and protein expression were used: (1) normal (S1T3), (2) pre-tumoral with low invasive potential (S2T2) and (3) tumoral with high metastatic potential (NS2T2A1). 26 In this model, we have previously demonstrated that PTHrP mRNA and protein expression were increased in the tumorigenic cell lines and that PTHrP stimulated proliferation in an autocrine fashion in the highly tumorigenic NS2T2A1 cell line. 27 Moreover, P2-initiated transcripts were only detected in the neoplastic lines.…”
Section: Resultsmentioning
confidence: 87%
“…In contrast, S2T2 cells, which also did not grow in soft agar, produced slow growing tumors (<8 mm in diameter 8 to 10 weeks after inoculation) in nude mice. The NS2T2A1 cell line was derived from an S2T2 tumor that had been grown in nude mice, reestablished in vitro and then repassaged in nude mice (Berthon et al 1992, Cataisson et al 2000. The NS2T2A1 line produced colonies in soft agar and tumors that grew rapidly in nude mice.…”
Section: Pthrp In Different Breast Cell Modelsmentioning
confidence: 99%
“…All the cell lines stained for pan-cytokeratin and cytokeratin 18, confirming their epithelial nature. S2T2 and NS2T2A1 cells exhibit specific chromosomal markers resembling those of human breast cancer (Berthon et al, 1992). Cells were cultured in Dulbecco's modified Eagle's and Ham's F12 medium (DMEM/F12, 1/1, v/v) with reduced calcium, 10 mM HEPES, 2 mM glutamine, 10 mg/ml insulin, 5mM cortisol, 2 ng/ml epidermal growth factor, 50 IU/ml penicillin, 50 mg/ ml streptomycin and 5% Chelex-treated horse serum.…”
Section: Pthrp In Different Breast Cell Modelsmentioning
confidence: 99%